Hussein Al-Faiz receives 2 Excellence Awards - Nor Salwana, Mohammad Idris (2022)
KUANTAN, August 6, 2022 - A keen interest in robotics has resulted in a double success for Hussein Al-Faiz Mohamed Ahmed Hafez, 26, who is a graduate of the Bachelor (Hons) Automotive Engineering - Collaboration Program with the University of Applied Sciences, Germany when he received two awards at the UMP 16th Convocation Ceremony.